A case report of successful thrombolytic therapy in stuck mechanical mitral valve in a case of post mitral valve replacement with severe left ventricular dysfunction - Sharma, Munish; Pandit, Anupam (International Journal of Advances in Medicine, 2025)
Stuck mechanical heart valves had always been tricky to manage and there has been always a debate on how to proceed with management plan. There is uncertainty regarding the type of thrombolytic agent, its dose, and rate of administration. We are reporting a case of stuck mitral valve with extremely low left ventricular ejection fraction (LVEF) which was successfully thrombolyzed using slow thrombolytic regimen. 57 years old lady, an old case of rheumatic heart disease (RHD) with severe mitral stenosis (MS), post mitral valve replacement (mechanical SJM 29 mm) in 2013, has presented with breathlessness New York Heart Association (NYHA) class 3 since 15 days. She has history of drug default. Clinically she was in heart failure and heart sounds were muffled (no clicks). On suspicion of stuck mitral valve urgent 2D ECHO was done which confirmed stuck mitral valve leaflet, with a high mean pressure gradient across prosthetic mitral valve (MV) (18 mmHg). She had severe Pulmonary arterial hypertension with maximum gradient right ventricular systolic pressure (RVSP) of 60 mm. LVEF was 20%. Fluoroscopy is not available at our centre. She was urgently thrombolysed with 25 mg alteplase over 06 hours along with unfractionated heparin infusion @1000 u/hour for 24 hours. 2D ECHO was repeated after 24 hours which revealed leaflets of mitral valve moving freely, with MVA >2 cm2. Mean gradient was reduced to 4 mm Hg across mitral valve. Pulmonary arterial hypertension (PAH) has reduced to 36 mm. LVEF has improved to 35%. Patient has been in follow up for more than a year with sustained results. Thrombolytic agents are a good alternative for stuck mechanical valves especially when cardiothoracic surgery is unavailable at remote centres.